Partial response to lorlatinib in thoracic inflammatory myofibroblastic tumor harboring complex and rare ALK fusions: a case report - Tang, Li-Bo; Peng, Ying-Long; Yang, Xiao-Rong; Li, Jia-Ting; Lu, Chang; Zheng, Mei-Mei; Sun, Lu; Yang, Zheng; Yan, Li-Xu; Deng, Yu; Chen, Zhi-Hong; Lv, Si-Di; et al. (Translational lung cancer research, 2025)
Targeted therapy has dramatically altered the treatment paradigm for some patients with inflammatory myofibroblastic tumor (IMT) that possesses specific molecular aberrations. IMT is an exceedingly rare type of sarcoma, with about 50% of cases featuring anaplastic lymphoma kinase ( ) gene rearrangements. The treatment of IMT with ALK fusions using ALK tyrosine kinase inhibitors (TKIs) has become increasingly common. However, until now, there is a lack of evidence supporting the efficacy of third-generation ALK-TKIs in this disease category. Here, we report the first case of a patient with advanced IMT harboring the EML4-ALK fusion gene along with two rare ALK fusion genes: PLB1-ALK, which has only been reported in two cases of lung adenocarcinoma and large cell neuroendocrine carcinoma, and unreported ALMS1-ALK. The patient achieved partial response (PR) following first-line treatment with lorlatinib and subsequently underwent successful surgical intervention. This is the inaugural case of a third-generation ALK-TKI achieving therapeutic success in advanced IMT with complex ALK rearrangements, including rare and previously uncharacterized fusion subtypes. Although the biological functions of these two rare ALK fusions still need to be confirmed, this case underscores the dependency of ALK-rearranged IMT on ALK-mediated signaling, suggesting that third-generation ALK-TKIs may offer an optimal targeted therapeutic strategy for ALK-dependent mesenchymal tumor subtypes.